2022
DOI: 10.1177/10732748221115236
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Markers Have Important Value in Predicting Relapse in Patients with papillary thyroid carcinoma: A Long-Term Follow-Up Retrospective Study

Abstract: Purpose Many markers of inflammation are increasingly found to have prognostic significance in some cancers. This study investigated the prognostic value of albumin/globulin (AGR), lymphocyte/monocyte ratio (LMR), and other inflammatory markers, including neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR), in patients with papillary thyroid carcinoma (PTC). Methods We retrospectively analyzed the data of 764 patients newly diagnosed with PTC (608 women, 156 men) aged 10-83 years. Univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Several previous research reports also confirmed our similar conclusion. A higher relative ratio of monocytes in THCA patients tends to be associated with a higher risk of postoperative recurrence, [ 45 ] and the relative ratio is also higher in THCA patients with lymph node and distant metastases. [ 46 ] Gogali F et al [ 47 ] found higher NK cell infiltration levels in papillary thyroid carcinoma (PTC) tissues, and NK cell infiltration levels were positively correlated with PTC clinical stage.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous research reports also confirmed our similar conclusion. A higher relative ratio of monocytes in THCA patients tends to be associated with a higher risk of postoperative recurrence, [ 45 ] and the relative ratio is also higher in THCA patients with lymph node and distant metastases. [ 46 ] Gogali F et al [ 47 ] found higher NK cell infiltration levels in papillary thyroid carcinoma (PTC) tissues, and NK cell infiltration levels were positively correlated with PTC clinical stage.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a well-established risk factor for many malignancies, and there are sex differences in thyroid inflammation that begin around puberty [ 78 ]. Thyroid inflammation due to autoimmune disorders is more common in women, and several studies have demonstrated that women with these disorders have an increased risk of thyroid cancer [ 79 , 80 ]. With that, investigations into the role of sex hormones in inflammation and the role of AR activation have uncovered mechanisms, including the inhibition of NFKB activation, and the suppression of T cells, macrophages, neutrophils, and natural killer cells, and hence, a reduction in inflammatory cytokine production [ 81 , 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the factors related to malignancy, the host immune system may be tightly involved in tumorigenesis, so suppressing the immune response is required to stop the development of the neoplasm. Recently, several systemic inflammatory markers, such as the neutrophil-to-lymphocyte ratio (NLR), the platelet-to-lymphocyte ratio (PLR) and the lymphocyte-to-monocyte ratio (LMR), have been considered predictive and prognostic factors for lung cancer, colorectal cancer, pancreatic cancer, breast cancer and, at least partially, for thyroid cancer [ 10 , 11 ]. In PTC, the predictive value of NLR has not yet been fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In PTC, the predictive value of NLR has not yet been fully investigated. Therefore, the incorporation of the NLR into a prognostic and predictive model might improve the stratification and management of indeterminate risk patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%